Expression, Truth and Authenticity: On Adorno's Theory of Music and Musical Performance - Vieira de Carvalho, Mário (Lisbon Colibri Universidade Nova de Lisboa, Centro de Estudos de Sociologia e Estética Musical, 2009)
Theodor W. Adorno (1903-1969) is one of the most representative German philosophers of the 20th century and of the so-called Frankfurt School. Amongst the main topics of his critical thinking is aesthetic theory, which he developed in particular in many of his essays on music. By dealing mainly with Adorno's theory of music and musical performance, the essays collected in this book offer critical insights not only into his approach to music, but also his philosophy as a whole. Adorno's theory of music and musical performance does not merely exemplify his aesthetic theory, but, rather, plays an essential role in the development of it and of his critical approach to culture and society. The constellation in which Adorno's unity of thought comes to light presupposes, in fact, an essential relationship between his theory of art and his social theory. Starting from expression, truth and authenticity as key concepts, relevant aspects of Adorno's musical thought are approached critically in this volume; the link between music and language, and the speech-character of art; meaning, mimesis, idiom, and their role in musical interpretation; fetishism, phantasmagoria, and the idea of unity of arts; new music and the culture industry; the relation between ethics and aesthetics; the critique of quotation. Adorno is confronted with Nietzsche, Lyotard and Wittgenstein. Particular emphasis is given to the discussion of his approaches to Schubert, Wagner, Mahler, Berg and Strauss.
Keywords: Adorno, Theodor W. -- 1903-1969; 20th Century (1901-2000); Music philosophy and esthetics; Performance